Municipality-Level Source Apportionment of PM2.5Concentrations Based on the CAPSS 2016: (VI) Chungcheongbuk-do - Son, Kyuwon; Kang, Yoon Hee; You, Seunghee; Kim, Eunhye; Bae, Minah; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2021)
The CAMx-PSAT (Comprehensive Air Quality Model with eXtensions-Particulate Source Apportionment Technology) simulation was applied to examine the inter- and intra-contributions to the concentrations of PM2.5and its components in eleven local authorities in Chungbuk during 2016. The domestic contribution to the annual mean PM2.5in the local authorities in Chungbuk ranged from 7.4 μg/m3(Danyang-gun) to 12.9 μg/m3(Eumseong-gun). The Chungbuk’s selfcontribution (2.6 μg/m3) to the annual PM2.5mean concentration was higher than those of the individual neighboring provinces; Chungnam 2.5 μg/m3, Gyeonggi 1.9 μg/m3, and Gyeongbuk 0.9 μg/m3. Note that the contribution of Chungnam became larger than Chungbuk’s for the high PM2.5days (>35 μg/m3), especially in local authorities in the vicinity of the upwind provinces. The combined inter- and intra-contributions also increased during the high PM2.5days (6.2 μg/m3for the daily mean≤35 μg/m3→ 12.3 μg/m3for the daily mean>35 μg/m3). Among PM2.5components, the self-contribution was important for ammonium and primary PM2.5in Chungbuk. Chungnam was, however, the main nitrate and sulfate contributor for the province. It implies that the cooperation with the neighboring provinces is helpful to alleviate the annual mean PM2.5concentration and to reduce the occurrence of the high PM2.5days in Chungbuk.
Keywords: Chungbuk; Foreign contribution; Neighbor contributions; PM2.5; Self-contribution